Pengaruh Model Pembelajaran Berbasis Proyek dalam Tatanan Group Investigation Terhadap Berpikir Tingkat Tinggi Di USI Pematangsiantar - Piliang, Fenny Mustika (Jurnal Pendidikan Biologi, 2017)
This study aims to determine the effect of Group Investigation with Project Based Learning model towards higher order thinking. The population of this research were the total, 60 under-graduated students of Simalungun University in fourth semester. They grouped as first experimental class treated by Group Investigation combine with PJBL, for next experimental class taught by Group Investigation and for control class taught by using conventional learning model. The research instrument uses a test result of learning ability of higher order thinking. This study include quasi experimental method. The data were analyzed by helping SPSS 21.0 program using F-test (ANACOVA Î± = 5% ). The results shown that: The higher order thinking ability of under-graduated students of Simalungun University treated by Group Investigation were significantly high (88,60 Â± 3,73; xÌ Â± SD) than group investigation class (81,00 Â± 4,01 (xÌ Â± SD) and conventional class 74,60 Â± 3,58 (xÌ Â± SD) with (Fhitung=67,742; P=0,000). Therefore, it can be concluded that Group Investigation combine with PJBL were affected the studentsâ higher order thinking abilities